The use of local anaesthetics in dermatology, aesthetic medicine and plastic surgery: review of the literature - Rękas-Dudziak, Anna; Męcińska-Jundziłł, Kaja; Walkowiak, Krzysztof; Witmanowski, Henryk (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
The aim of the study is to present the latest information on local anaesthesia in plastic surgery, aesthetic medicine and dermatology based on the available literature. The aim of the work is to present a model of cooperation between an anaesthesiologist, dermatologist, and surgeon, so that the patients feel safe, and, above all, the procedure will be comfortable and painless for them. Regional blocks are an excellent tool to achieve this goal. Achieving this requires commitment and understanding by both the plastic surgeon and the anaesthesiologist.